Offline Routing and Wavelength Assignment in Transparent WDM Networks - Christodoulopoulos, Konstantinos; Manousakis, Konstantinos; Varvarigos, Emmanouel (IEEE/ACM transactions on networking, 2010)
We consider the offline version of the routing and wavelength assignment (RWA) problem in transparent all-optical networks. In such networks and in the absence of regenerators, the signal quality of transmission degrades due to physical layer impairments. Because of certain physical effects, routing choices made for one lightpath affect and are affected by the choices made for the other lightpaths. This interference among the lightpaths is particularly difficult to formulate in an offline algorithm since, in this version of the problem, we start without any established connections and the utilization of lightpaths are the variables of the problem. We initially present an algorithm for solving the pure (without impairments) RWA problem based on a LP-relaxation formulation that tends to yield integer solutions. Then, we extend this algorithm and present two impairment-aware (IA) RWA algorithms that account for the interference among lightpaths in their formulation. The first algorithm takes the physical layer indirectly into account by limiting the impairment-generating sources. The second algorithm uses noise variance-related parameters to directly account for the most important physical impairments. The objective of the resulting cross-layer optimization problem is not only to serve the connections using a small number of wavelengths (network layer objective), but also to select lightpaths that have acceptable quality of transmission (physical layer objective). Simulations experiments using realistic network, physical layer, and traffic parameters indicate that the proposed algorithms can solve real problems within acceptable time.